2011
DOI: 10.1111/j.1472-4642.2011.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollen transport differs among bees and flies in a human‐modified landscape

Abstract: Aim  Dispersal distances of insect pollinators are critical in defining their contribution to landscape‐wide pollen movement and ultimately gene flow in natural and agricultural systems. We ask whether bee and fly pollinator taxa differ in their dispersal distances and transport of viable pollen in a human‐modified system. Location  Canterbury and Otago region, South Island, New Zealand. Methods  We captured pollen‐carrying insects travelling outside of a model mass‐flowering agricultural crop, Brassica rapa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 95 publications
(181 reference statements)
6
91
0
Order By: Relevance
“…In particular, as honey bee abundance differed only slightly between homogeneous and heterogeneous landscapes, its contribution to crop pollination is expected to be more or less constant across our ten fields. Although hoverflies have been shown to contribute significantly to pollination in oilseed rape (Jauker and Wolters 2008;Rader et al 2011), a recent study shows that honey bees and wild bees are probably better pollinators of oilseed rape than hoverflies (Jauker et al 2012). Therefore, the pollinator species that contributed most was probably the honey bee, simply because it was the most abundant species in the fields.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, as honey bee abundance differed only slightly between homogeneous and heterogeneous landscapes, its contribution to crop pollination is expected to be more or less constant across our ten fields. Although hoverflies have been shown to contribute significantly to pollination in oilseed rape (Jauker and Wolters 2008;Rader et al 2011), a recent study shows that honey bees and wild bees are probably better pollinators of oilseed rape than hoverflies (Jauker et al 2012). Therefore, the pollinator species that contributed most was probably the honey bee, simply because it was the most abundant species in the fields.…”
Section: Discussionmentioning
confidence: 96%
“…Non-bee taxa, in particular, often have broader temporal activity ranges (34)(35)(36) and can provide pollination services at different times of the day compared with bees and in weather conditions when bees are unable to forage (37)(38)(39)(40). In addition, non-bee taxa may be more efficient in transferring pollen for some crops under certain conditions (18,19,38) and/or carry pollen further distances than some bees (41). It has been suggested that this long-distance pollen transfer could have important genetic consequences for wild plants (42,43).…”
mentioning
confidence: 99%
“…This scale has been used in previous studies to test for effects of landscape elements on the abundance, composition and diversity of insects visiting crop fields, for example by Letourneau and Goldstein (2001) for herbivores, predators and parasitoids; Thies et al (2003) for herbivores and parasitoids; and Kremen et al (2004) for native bees. Most parasitoids can disperse across several kilometers (e.g., Munro, 1998), and trivial movement distances are likely to cover hundreds of meters and vary among species in such large and diverse families (Brodmann et al, 1997;Roth et al, 2006;Rader et al, 2011). Thus, landscape characteristics within 0.5 km may be the most relevant scale for frequented refugia, but both the 500m and 1500m scales quantified in our vegetation analysis are likely within the potential dispersal range of many of these parasitoids.…”
Section: Study Sitesmentioning
confidence: 95%